Diagnostic inference based on predicted effective trajectory - Będkowski, Lesław; Dąbrowski, Tadeusz (Zielona Góra: Uniwersytet Zielonogórski)
The technical and operational state of a object is characterized by so called describing quantity set. Those quantities among others are random functions' of time. Each of the describing quantities has an upper and a lower constraint. Using an object in a time interval ?T guarantees the achievement of a reliable effect (product). The effect value is a random function of the initial describing quantity values, describing a quantity process of realization of changes in the ?T time interval, constraint function realizations, random failure distribution and also the object operation time ?T.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka